Xalq pedagogikasi vatanparvarlik tuyg‘ularini shakllantirish vositasi (SCIENCE and SOCIETY, 2024)
The article pays attention to the role of children’s folklore in patriotic education, development, formation and maturation of primary school students, as well as the opinions of some researchers on these issues.